The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
Cochrane Database of Systematic Reviews 2014
DOI: 10.1002/14651858.cd002783.pub3
|View full text |Cite
|
Sign up to set email alerts
|

Thrombolysis for acute deep vein thrombosis

Abstract: Background Standard treatment for deep vein thrombosis aims to reduce immediate complications. Use of thrombolysis or clot dissolving drugs could reduce the long-term complications of post-thrombotic syndrome (PTS) including pain, swelling, skin discolouration, or venous ulceration in the affected leg. This is the third update of a review first published in 2004. Objectives To assess the effects of thrombolytic therapy and anticoagulation compared to anticoagulation alone for the management of people with acut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
65
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 99 publications
(70 citation statements)
references
References 36 publications
2
65
0
3
Order By: Relevance
“…11 However, there is also a significantly increased risk of bleeding complications (RR: 2.23, 95% CI: 1.41-3.52) with CDT, including fatal or intracranial bleeding. The degree of residual clot following CDT has been correlated with the risk for developing PTS.…”
Section: Endovascular Therapy Optionsmentioning
confidence: 99%
“…11 However, there is also a significantly increased risk of bleeding complications (RR: 2.23, 95% CI: 1.41-3.52) with CDT, including fatal or intracranial bleeding. The degree of residual clot following CDT has been correlated with the risk for developing PTS.…”
Section: Endovascular Therapy Optionsmentioning
confidence: 99%
“…13 Thrombolytic treatment effectively dissolves the thrombus and reduces postthrombotic syndrome (RR: 0.66; 95%CI: 0.47-0.94), but it is associated with a higher frequency of hemorrhagic complications. 12 The ATTRACT study 18,19 randomized 692 patients with proximal DVT for fibrinolytic treatment or conventional treatment (anticoagulants and elastic stockings). After 2 years it was observed that fibrinolytic treatment did not prevent postthrombotic syndrome, but did reduce its severity in 25% of cases (18% vs. 24%).…”
Section: Discussionmentioning
confidence: 99%
“…Possible treatment options that were considered for these cases included: anticoagulant treatment 3,11 ; fibrinolytic treatment or thrombolysis 12 ; and inferior vena cava filter (VCF).…”
Section: Part I -Clinical Situationsmentioning
confidence: 99%
“…Carefully selected patients with low bleeding risk (often younger patients) with extensive proximal iliofemoral DVT may benefit from thrombolysis, particularly CDT, in which bleeding rates are lower than the systemic thrombolytic therapy [143][144][145][146]. CDT should be considered for patients with symptomatic iliofemoral DVT who have symptoms of less than 14-day duration, good functional status, a life expectancy of 1 year or more and a low risk of bleeding.…”
Section: ) Compression Therapymentioning
confidence: 99%